2019
DOI: 10.5194/acp-2019-699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A predictive group-contribution model for the viscosity of aqueous organic aerosol

Abstract: <p><strong>Abstract.</strong> The viscosity of primary and secondary organic aerosol (SOA) has important implications for the processing of aqueous organic aerosol phases in the atmosphere, their involvement in climate forcing, and transboundary pollution. Here we introduce a new thermodynamics-based group-contribution model, which is capable of accurately predicting the dynamic viscosity of a mixture over several orders of magnitude (~ 10<sup&… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…5). These viscosities are in the typical range for SOA under dry conditions and fall into the semi-solid phase state region (Koop et al, 2011;Shiraiwa et al, 2011;Abramson et al, 2013;Zhang et al, 2015b;Grayson et al, 2016;Gervasi et al, 2019). Using the Stokes-Einstein relation (Einstein, 1905) and an effective molecular radius of 2 nm, these viscosities correspond to bulk diffusion coefficients of 5×10 −16 to 5×10 −18 cm 2 /s at 298 K. The effective radius is approximated from geometric considerations assuming spherical molecular shape, a molar mass of 250 g/mol and density of 1.55 g/cm 3 .…”
Section: Mass Transfer Limitationsmentioning
confidence: 91%
See 1 more Smart Citation
“…5). These viscosities are in the typical range for SOA under dry conditions and fall into the semi-solid phase state region (Koop et al, 2011;Shiraiwa et al, 2011;Abramson et al, 2013;Zhang et al, 2015b;Grayson et al, 2016;Gervasi et al, 2019). Using the Stokes-Einstein relation (Einstein, 1905) and an effective molecular radius of 2 nm, these viscosities correspond to bulk diffusion coefficients of 5×10 −16 to 5×10 −18 cm 2 /s at 298 K. The effective radius is approximated from geometric considerations assuming spherical molecular shape, a molar mass of 250 g/mol and density of 1.55 g/cm 3 .…”
Section: Mass Transfer Limitationsmentioning
confidence: 91%
“…The high viscosity caused by limonene oxidation products might in turn affect evaporation in the mixed precursor experiments and cause the observed non-linear effects. In a first approximation, viscosities of mixtures can be assumed to be a linear combination of the individual viscosities and follow a logarithmic mixing rule (Gervasi et al, 2019). This entails that the change in the rate of mass transport between pure compounds and their mixtures can reach orders of magnitudes.…”
Section: Mass Transfer Limitationsmentioning
confidence: 99%
“…Additionally, adequate consideration of liquid-liquid separations as well as salt formation (crystallization) in deliquesced aerosol particles is also necessary, which can potentially alter the ionic strength and acidity, and thus influence non-ideality. Moreover, model advancements are necessary by extending the database with new organic and inorganic AIOMFAC interaction parameters (Ganbavale et al, 2015;Gervasi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it has to be noted that the current version of SpactMod does not consider the latest development stage of the AIOMFAC model (Ganbavale et al, 2015;Gervasi et al, 2019). Nevertheless, it has also been observed that SPACCIM-SpactMod allows for model simulations with and without consideration of non-ideality by treating molarities as concentrations and activities, respectively.…”
Section: Multiphase Chemistry Model Spaccim-spactmodmentioning
confidence: 99%
“…(1) was developed based on the training dataset containing a large number of compounds with measured C 0 (Table S1 in Supplement) and aimed to be applied in the 2D-VBS framework to predict the viscosity of SOA mixtures. For pure organic compounds with known molecular structure, viscosity can be predicted by group contribution approaches (Cao et al, 1993;Bosse, 2005;Song et al, 2016b;Gervasi et al, 2019;Rovelli et al, 2019).…”
Section: Parameterizationsmentioning
confidence: 99%